PEMBUATAN MINUMAN PROBIOTIK AIR KELAPA MUDA (Cocos nuciferra L) DENGAN STARTER Lactobacillus casei subsp. casei R-68 - Anwar, Muhammad Zainul; Pato, Usman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Young coconut water probiotic drink is one of fermented beverage products containing probiotic bacteria. Young coconut water contains nutrients such as carbohydrates, moisture, fat, proteinand ash contents, that can be combined with the addition of sugar as a source of nutrients for the growth of lactic acid bacteria. The purpose of this research was to evaluate Â the effect of variation sucrose using starter Lactobacillus casei subsp. casei R-68 on the quality of probiotic drink of young coconut water. This research was conducted experimentally using Completely Randomized Design with 5 treatments and 3 replications. The treatments in this study were G1 (100 ml coconut water + 0% sugar), G2 (young coconut water 100 ml + 2% sugar), G3 (young coconut water 100 ml + 4% sugar), G4 (water Young coconut 100 ml + sugar 6%) and G5 (young coconut water 100 ml + sugar 8%). The results show that variation of sucrose concentration significantly affected pH value, total lactic acid, total lactic acid bacteria, total sugar, ash, colour, flavour, taste and overall acceptance of probiotic drink. The best treatment was G5 (young coconut water 100 ml + 8% sugar), with pH 4.36, total lactic acid 0.43%, total LAB 10.23 cfu/ml, total sugar 10.36%, and ash content 0.71%. The probiotic drink of G5 treatment was favored by panelists with cloudy white colour (3.93), young and acidic coconut water flavour (3.63), sweet taste (3.60). Overall assessment hedonik test of young coconut water probiotic drink was preferred by th e panelists.Â Keywords: probiotics, young coconut water, Lactobacillus casei subsp. casei R-68.Â